2016
DOI: 10.1103/physrevlett.117.016801
|View full text |Cite
|
Sign up to set email alerts
|

Location of Trapped Electron Centers in the Bulk of Epitaxial MgO(001) Films Grown on Mo(001) Usingin situW-band Electron Paramagnetic Resonance Spectroscopy

Abstract: We present the first in situ W-band (94-GHz) electron paramagnetic resonance (EPR) study of a trapped electron center in thin MgO(001) films. The improved resolution of the high-field EPR experiments proves that the signal originate from a well-defined species present in the bulk of the films, whose projection of the principal g-tensor components onto the (001) plane are oriented along the [110] direction of the MgO lattice. Based on a comparison between the structural properties of the films, knowledge of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Figure 8(b) shows a comparison between X-band (top) and W-band spectra (below) of MgO color centers located in the bulk of the MgO film. From a detailed g-tensor analysis as well as angle dependent measurements (see Figure 8(c)), we concluded that those species are located at screw dislocations inside the MgO film [26].…”
Section: Oxide Model Supportsmentioning
confidence: 84%
See 4 more Smart Citations
“…Figure 8(b) shows a comparison between X-band (top) and W-band spectra (below) of MgO color centers located in the bulk of the MgO film. From a detailed g-tensor analysis as well as angle dependent measurements (see Figure 8(c)), we concluded that those species are located at screw dislocations inside the MgO film [26].…”
Section: Oxide Model Supportsmentioning
confidence: 84%
“…In order to improve on resolution, it was necessary to move to higher magnetic fields (W-band, 94 GHz). The reduced wavelength of the radiation introduces additional constraints which required to develop an appropriate re-sonator structure [25,26]. However, it has been possible to set up a working spectrometer (Figure 3(b)) and proving its ability to improve spectral resolution using color centers in oxides as a model system.…”
Section: Instrument Developmentmentioning
confidence: 99%
See 3 more Smart Citations